Association of Tumor Necrosis Factor Alpha and Lymphotoxin Alpha Gene Polymorphisms with the Presence of Chronic Obstructive Pulmonary Disease - Amira P Tarigan; Tamsil Syafiuddin; Faisal Yunus; Suradi Suradi (Interna Publishing, 2015)
Aim: to analyze the occurrence of chronic obstructive pulmonary disease (COPD) and its association with the polymorphisms of -308G/A, -238G/A of TNFα gene and +252A/G LTα gene polymorphism in smokers. Methods: cross-sectional study, comparing the genetic group of people who have COPD and who do not have COPD with the same smoking history. The study was conducted from January 2011 to March 2012 at several health centers; such as Adam Malik Hospital, Pirngadi Hospital, Tembakau Deli Hospital, Siti Hajar Hospital in Medan and several health centers in the city of Medan. Examination of lung function was done using spirometry and the existence of genetic polymorhisms in the TNFα and LTα gene was performed using polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP). Results: of the total of 227 samples that met inclusion criteria and after equalizing the age and history of smoking, 186 subjects were enrolled, of which, 93 people as COPD group and 93 people as non-COPD group. Analysis of the association between the -308G/A polymorphism with the COPD revealed the odds ratio (OR) 0.436 (95% CI 0.224-0.850, p=0.014). Polymorphism at -238G/A of the TNFα gene showed the OR 2.094 (95% CI 0.608 - 7.211, p=0.241). Polymorphism at +252A/G LTα gene showed OR 1.256 (95% CI 0.694 - 2.272; p=0.450). The findings indicated that polymorphism at -308G showed a protective factor whereas the -238G/A of the TNFα and +252A/G of the LTα genes did not show any significant association with the COPD. Conclusion: polymorphism -308 TNFα gene shown to be a protective factor for the occurrence of COPD. Polymorphism -238 TNFα gene and +252 LTα gene did not show any significant association with COPD. Key words: chronic obstructive pulmonary disease, TNFα gene, LTα gene, polymorphism.